Rates of Armezon Pro for Postemergence Weed Control in Fallow - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several tank mixes of Armezon in fallow. Control of kochia and Russian thistle generally increased as Armezon Pro (topramezone + dimethenamid) rates increased from 14 to 20 oz/a. Although these herbicides injured the weeds present, smaller weeds will need to be targeted for effective control. The population of kochia was too thick and the size of the weeds was too large to allow enough coverage for this product to work under the conditions of this trial. The level of tissue damage suggests that further testing is needed with smaller weeds in a thinner population.
Keywords: Herbicide titration